Biochemical and transcriptomic profiling analysis of drought tolerant related genes in ML 82-2 and ML 125-2 rice mutant lines - Jun Ying Low; Rhun Yian Koh; Sobri Hussein; Ahmad Faiz; Anna Pick Kiong Ling (BioTechnologia)
Background Backcrossing of gamma-irradiated IS21 with MR220 has generated progenies (ML 82-2 and ML 125-2) with improved traits. However, studies on these new mutant lines remain limited. This study aimed to determine and compare the biochemical characteristics and transcriptomic profiles of drought-tolerance-related genes in ML 82-2 and ML 125-2, as well as in the parent lines, IS21 and MR220.